Linking Authoritative and Micromanaging Leadership to Retention: Does Employee Engagement Bridge the Gap? - Wei Yee Ngan; Hemaloshinee Vasudevan (Journal of Organizational and Human Resource Development Strategies, 2026)
In a business organization, diverse individuals with specific roles are crucial for operations and growth, and MSMEs are predominant in the Malaysian economy. There is a significant gap in empirical research regarding the combined effects of authoritative and micromanaging leadership on employee engagement and retention in business organizations. While individual studies exist on each leadership style, their joint impact in dynamic organizational contexts is still not well understood. The study aims to analyze the effects of authoritative and micromanaging leadership styles on employee engagement and retention in small and medium enterprises (SMEs) in Malaysia, where SMEs represent a significant portion of businesses. This study employed an online survey with a structured questionnaire, resulting in a purposeful sample of 121 participants. This survey gathers information from ten SMEs across various sectors, including sales and marketing, information technology, investment, investment holdings, travel, entertainment, and social enterprise. There are seven hypotheses in this study. Four hypotheses are accepted, while three are rejected. These findings indicate that in the sampled SMEs, authoritative leadership behaviors alone do not sufficiently increase employees' emotional involvement or long-term commitment. Organizations should reduce micro-management and adopt leadership practices that foster trust, autonomy, and open communication. Management needs to focus on engagement-oriented leadership development, encourage delegation, and establish supportive work environments to enhance employee engagement, which is crucial for long-term retention and organizational stability.